NEVOD as a test facility for future neutrino telescopes - Petrukhin A.A.; Khokhlov S.S. (EPJ Web of Conferences, 2019)
The possibility to calibrate the new optical modules mDOM of the IceCube-Upgrade neutrino telescope inside the tank of Cherenkov water detector NEVOD is discussed. Methods to calibrate optical modules are presented. The spatial lattice of the detector NEVOD and deployed outside of the water tank calibration telescope system and coordinate-tracking detector DECOR allow calibrating the response of mDOM with respect to the Cherenkov light from muons, muon bundles and cascades with known trajectories.